Development of human resources (HR) on work ethic and employee performance at PT. Citilink Indonesia - Haryati, Endri (Trigin Publisher, 2024)
Human resources (HR) are a very important component and cannot even be separated from a company; HR is an important asset for every business because it determines the success of a company in achieving its business goals. If high-quality human resources exist within an organization, they can be an important asset that can provide unlimited support in the future. Company performance is the level of achievement of results in achieving goals, while individual performance is the level of achievement of results in carrying out certain tasks. PT Citilink Indonesia, a strategic subsidiary of Garuda Indonesia, was founded in 2009 and is one of the best low-cost airlines (LCC) in Indonesia. This research uses descriptive qualitative methods. The focus of this research is to provide an in-depth overview of human resource (HR) training and development at PT Citilink Indonesia. To achieve this goal, this research uses a direct observation approach to activities or circumstances related to HR training and development in the company (Observation). Therefore, PT Citilink Indonesia effectively implements competency-based HR training and development to meet the needs of all its employees